2006
DOI: 10.1128/aac.00722-06
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Ceftobiprole against Aerobic and Anaerobic Strains Isolated from Diabetic Foot Infections

Abstract: Against 443 aerobic and anaerobic bacteria isolated from diabetic foot infections, ceftobiprole MICs (g/ml) at which 90% of the isolates tested were inhibited were as follows: methicillin-resistant Staphylococcus aureus, 1; methicillin-susceptible S. aureus and Staphylococcus lugdunensis, 0.5; Anaerococcus prevotii, 0.125; Finegoldia magna, 0.5; Peptoniphilus asaccharolyticus, 1; Peptostreptococcus anaerobius, 4; Escherichia coli and Enterobacter species, 0.125; Klebsiella species, 2; and Pseudomonas aeruginos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 9 publications
0
46
0
Order By: Relevance
“…In addition, one S. lugdunensis isolate was resistant to erythromycin. There have also been single reports of S. lugdunensis isolates resistant to streptomycin (86), tetracycline (183), penicillin (183), gentamicin (83), ceftazidime (74), and aminoglycosides and macrolides (60). A single case report described the emergence of resistance to rifampin and ciprofloxacin that correlated with treatment of a persistent S. lugdunensis infection that manifested over 3 years as septic arthritis of both knees, vertebral osteomyelitis, and aortic and mitral valve endocarditis (98).…”
Section: Antimicrobial Susceptibility Prevalence Of Antimicrobial Resmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one S. lugdunensis isolate was resistant to erythromycin. There have also been single reports of S. lugdunensis isolates resistant to streptomycin (86), tetracycline (183), penicillin (183), gentamicin (83), ceftazidime (74), and aminoglycosides and macrolides (60). A single case report described the emergence of resistance to rifampin and ciprofloxacin that correlated with treatment of a persistent S. lugdunensis infection that manifested over 3 years as septic arthritis of both knees, vertebral osteomyelitis, and aortic and mitral valve endocarditis (98).…”
Section: Antimicrobial Susceptibility Prevalence Of Antimicrobial Resmentioning
confidence: 99%
“…Fifteen bloodstream isolates exhibited susceptibility to many common antimicrobials, including penicillin (51). Fifteen S. lugdunensis isolates from diabetic foot infections were susceptible to eight out of nine agents tested, including ceftobiprole, a new broad-spectrum cephalosporin (74).…”
Section: Antimicrobial Susceptibility Prevalence Of Antimicrobial Resmentioning
confidence: 99%
“…15,32 Ceftobiprole MIC 90 values of 8 to 16 µg/mL for ceftazidime-susceptible P. aeruginosa, while MIC 90 values of 16 to 64 µg/mL for ceftazidime-resistant isolates have been reported. 12,13,15,20 In the surveillance study published by Fristche et al 21 ceftobiprole was equal in potency to ceftazidime and 2-fold more potent than cefepime against P. aeruginosa. Pillar et al 18 reported that, as was observed with Enterobacteriaceae, the activity of ceftobiprole and cefepime against P. aeruginosa and Acinetobacter spp.…”
Section: 31mentioning
confidence: 99%
“…15 These results are consistent with those reported in other studies. 12,13,20 Ceftobiprole showed more activity than ceftriaxone against Citrobacter freundii and against Enterobacter cloacae.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation